1988
DOI: 10.1002/jhrc.1240110111
|View full text |Cite
|
Sign up to set email alerts
|

On‐line extraction and separation by supercritical fluid chromatography with packed columns

Abstract: The application of fluid extraction in combination with fluid chromatography with packed column and flame ionization detection is described. Fluid chromatographic equipment is shown. Applications of this system to drug characterization are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In SFE, carbon dioxide is used predominantly (KAL- LIO et al 1994;ENGELHARDT, GROSS 1988;BOUNOS-HITA et al 1993) for its low critical temperature (31°C) and pressure (7.38 MPa), non-toxicity, incombustibility 1996-1997 1997-1998 1998-1999 1999-2000 2000-2001 Harvest area (ha) 9,500 5,000 1,900 2,100 2,400…”
mentioning
confidence: 99%
“…In SFE, carbon dioxide is used predominantly (KAL- LIO et al 1994;ENGELHARDT, GROSS 1988;BOUNOS-HITA et al 1993) for its low critical temperature (31°C) and pressure (7.38 MPa), non-toxicity, incombustibility 1996-1997 1997-1998 1998-1999 1999-2000 2000-2001 Harvest area (ha) 9,500 5,000 1,900 2,100 2,400…”
mentioning
confidence: 99%
“…It is also the best known commercial application of SFE (caffeine from coffee) . Several publications describe the conditions and experimental arrangement necessary to extract caffeine from coffee or tea (Williams, 1981;Sugiyama et al, 1985;Skelton et al, 1986;Engelhardt and Gross, 1988;Jenkins et al, 1991). Since we do not wish to avoid this topic, an HPLC trace from one of the earlier analytical papers on the topic is shown in Figure 6.13 (Sugiyama et al, 1985).…”
Section: Caffeinementioning
confidence: 99%
“…SFC has been coupled with a number of separation techniques, such as SFC-SFC [23], SFC-GC [24], and SFE-SFC [25]. However, few studies have been reported about coupling SFC to HPLC, which is possibly due to the incompatibility of solvents and differences in operational pressure.…”
Section: Introductionmentioning
confidence: 98%